Remote work from a socio-spatial perspective: Co-working spaces as a chance for suburban and rural areas? - Krasilnikova, Nadezda; Levin-Keitel, Meike (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
The world of labour is undergoing major changes. With the processes of digitalisation, the possibilities to work flexibly wherever people live or spend their time are increasing. Digitalbased forms of work promote the development of mobile work in a self-determined location (e.g. in a home office or co-working space). Such location-independent forms of work offer new opportunities for further development of rural areas and especially small and medium-sized towns. The strategic (re) linking of living and working is in many respects both an opportunity and a challenge in equal measure: A shift in the centre of people’s lives can strengthen the place of residence in rural areas through increased (also) economic demand, through a mix of uses and a diversified demand for local supply or through a reduction of traffic loads, such as commuting. In this paper, we explore both the socio-spatial preconditions and the effects of this shift from places of work to places of residence in rural areas. The aim is to outline a systematic classification of co-working spaces with regard to sustainable spatial development in order to promote the opportunities of mobile work in different suburban and rural areas.
Keywords: Digitalisation of work; Remote work; Sociospatial perspective; Co-working space; Suburban area; Rural development